2009
DOI: 10.4067/s0717-95022009000100033
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Analyses of Caseous Necrosis Correlated to CD68+ and CD8+ Cells in Biopsies of Tuberculous Pleurisy

Abstract: SUMMARY:Tuberculosis is the most prevalent infectious disease in the world. Granuloma formation and caseous necrosis are hallmarks of M. tuberculosis infection and they represent the protective and inflammatory reactions in the infected tissues. The molecular mechanisms that mediate granuloma necrosis are still not well understood. Objectives: To immunolocalize and correlate the amounts of CD68+ macrophages and CD8+ lymphocytes to caseous necrosis extension in granulomas of tuberculous pleurisy. Methods: The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Granulomas seen in tuberculous pleurisy allow to distinguish the cellular components comparing the cells present in pleura fluid. 21 Fayyazi et al showed a possible apoptosis of epithelioid cells and the presence of CD4 T lymphocytes in the proximity of the focus of the necrosis. Such findings could suggest a direct relation between the cells, their secretions and the central necrosis of granulomas, in addition to the epithelioid cell's apoptosis.…”
Section: Initiation Of Infection and Granuloma Formationmentioning
confidence: 99%
“…Granulomas seen in tuberculous pleurisy allow to distinguish the cellular components comparing the cells present in pleura fluid. 21 Fayyazi et al showed a possible apoptosis of epithelioid cells and the presence of CD4 T lymphocytes in the proximity of the focus of the necrosis. Such findings could suggest a direct relation between the cells, their secretions and the central necrosis of granulomas, in addition to the epithelioid cell's apoptosis.…”
Section: Initiation Of Infection and Granuloma Formationmentioning
confidence: 99%